Requirement analysis of information system model for curriculum design - Thong, Chee Ling; Jusoh, Yusmadi Yah; Abdullah, Rusli; Alwi, Nor Hayati (Universiti Utara Malaysia, 2016)
Over recent years, there has been development of various information systems (IS) for curriculum design in Institution of Higher Learning (IHL). It has been recognized that IS can increase work efficiency in terms of reducing time, error and effort of curriculum designers. However, based on literature study it is found that there is a shortage of information system model in curriculum design. This study is conducted to propose an IS model by performing requirements analysis through the study of varoius IS in the domain of curriculum design. Strengths and limitations of these IS are identified and analyzed. Furthermore, a survey is conducted among 90 curriculum designers in 20 IHLs to perform verification on components of the model which identified though literature review. The findings show that these components are important components for the proposed IS model.